1993
DOI: 10.1090/s0002-9947-1993-1102888-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of completions of unique factorization domains

Abstract: Abstract. It is shown that a complete local ring is the completion of a unique factorization domain if and only if it is a field, a discrete valuation ring, or it has depth at least two and no element of its prime ring is a zerodivisor. It is also shown that the Normal Chain Conjecture is false and that there exist local noncatenary UFDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 6 publications
0
75
0
Order By: Relevance
“…Our construction is based on the techniques used in [3] and is inspired by the construction of Heitmann in [1]. We start with the prime subring of T , localized at the appropriate prime ideal.…”
Section: Introductionmentioning
confidence: 99%
“…Our construction is based on the techniques used in [3] and is inspired by the construction of Heitmann in [1]. We start with the prime subring of T , localized at the appropriate prime ideal.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of unique factorization domains whose completions are not unique factorization domains were known previously (see Fossum [5,Example 19.9] and Halanay [8]), but our examples seem particularly natural. In fact, Heitmann [9,Theorem 8] has shown that every complete local domain of depth at least two is the completion of a subring which is a unique factorization domain; this gives a wealth of complicated examples.…”
Section: Theorem 12 Let G Be a Finite Group And V Be A Direct Summamentioning
confidence: 99%
“…Suppose that T is the completion of a UFD A with semilocal generic formal fiber G. From Heitmann (1993), we know that T must be a field, a DVR, or have depth at least two and no integer of T is a zerodivisor. Now, let P ∈ Ass T with ht P > 0, and let Q be a prime ideal containing P such that ht Q = ht P + 1.…”
Section: Let T M Be a Complete Local Ring And T/m = T Then T Is Tmentioning
confidence: 99%
“…From Proposition 1 in Heitmann (1993), in order to make A complete to T , we must have IT ∩ A = I for every finitely generated ideal I of A. The following lemma helps us get this condition.…”
Section: Semi-local Formal Fibers At Height One Prime Idealsmentioning
confidence: 99%
See 1 more Smart Citation